2022
DOI: 10.1542/peds.2021-054268i
|View full text |Cite
|
Sign up to set email alerts
|

Masking Adherence in K–12 Schools and SARS-CoV-2 Secondary Transmission

Abstract: OBJECTIVES: Masking is an essential coronavirus 2019 mitigation tool assisting in the safe return of kindergarten through 12th grade children and staff to in-person instruction; however, masking adherence, compliance evaluation methods, and potential consequences of surveillance are currently unknown. We describe two school districts' approaches to promote in-school masking and the consequent impact on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) secondary transmission. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Reasons could include stricter adherence to rules while in schools and less time spent in households and other contact areas with a higher adult-to-child transmission. One study describes differential mask adherence of primary and secondary school students [ 50 ], however, without reporting confidence intervals or clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons could include stricter adherence to rules while in schools and less time spent in households and other contact areas with a higher adult-to-child transmission. One study describes differential mask adherence of primary and secondary school students [ 50 ], however, without reporting confidence intervals or clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Masking was only required for staff members outside the classrooms and not for children. A large study from the USA during dominance of the alpha variant found low secondary attack rates in schools with masking mandatory for both students and staff members [ 15 ]. Additionally, one study from Georgia USA found decreased COVID-19 incidence when school staff members were mandated to use masks [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Masking was only required for staff members outside the classrooms and not for children. A large study from the USA during dominance of the alpha variant found low secondary attack rates in schools with masking mandatory for both students and staff members [15]. Additionally, one study from Georgia USA found decreased COVID-19 incidence when school staff members were mandated to use masks [16].…”
Section: Discussionmentioning
confidence: 99%